2007
DOI: 10.1210/en.2007-1463
|View full text |Cite
|
Sign up to set email alerts
|

The Melanocortin 2 Receptor Accessory Protein Exists as a Homodimer and Is Essential for the Function of the Melanocortin 2 Receptor in the Mouse Y1 Cell Line

Abstract: The ACTH receptor [melanocortin 2 receptor (MC2R)] gene produces a functional receptor only when transfected into cells of adrenocortical origin, implying that it may require an adrenal-specific accessory factor. Recently we showed that the MC2R accessory protein (MRAP) is essential for the cell surface expression of the MC2R in such models. Using RNA interference (RNAi) technology, we have further explored the action of MRAP in the functioning of the MC2R in Y1 mouse adrenocortical cells that endogenously exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 26 publications
4
62
0
Order By: Relevance
“…The MRAP gene is encoding a protein of 172 residues and predicted molecular weight of 19 kDa. MRAP forms a stable antiparallel homodimer at the plasma membrane and in the ER and shows glycosylation of the protein (Sebag & Hinkle 2007, Cooray et al 2008. In the present study, both anti-V5 antibody and anti-MRAP antibody detected the bands in H295RA cells between 30 and 40 kDa on western blotting.…”
Section: Disscusionsupporting
confidence: 57%
See 2 more Smart Citations
“…The MRAP gene is encoding a protein of 172 residues and predicted molecular weight of 19 kDa. MRAP forms a stable antiparallel homodimer at the plasma membrane and in the ER and shows glycosylation of the protein (Sebag & Hinkle 2007, Cooray et al 2008. In the present study, both anti-V5 antibody and anti-MRAP antibody detected the bands in H295RA cells between 30 and 40 kDa on western blotting.…”
Section: Disscusionsupporting
confidence: 57%
“…In fact, a previous study demonstrated that endogenously expressed Y-1 adrenal cell MRAP was immunodetected as a band of more than 30 kDa despite the predicted molecular mass of 14 kDa (Cooray et al 2008). H295RA cells showed higher basal MC2R expression levels and greater response to ACTH stimulation compared to the parental H295R cells in terms of steroidogenesis and mRNA expression of steroidogenic enzymes.…”
Section: Disscusionmentioning
confidence: 95%
See 1 more Smart Citation
“…Human MRAP1 existed as one of two splice variants -MRAP1 α and β that had distinct 3′ ends encoding different C-termini. We found MRAP1 existed as a very stable dimer that was relatively resistant to dissociation by detergents and reducing agents (Cooray et al 2008). Remarkably, Sebag and Hinkle (2007) demonstrated using a number of techniques that this was an antiparallel homodimer in which one N-terminus was extracellular and the other intracellular.…”
Section: The Discovery Of Mrapmentioning
confidence: 76%
“…The functional expression of MC2R requires the MC2R accessory protein (MRAP), a protein involved in the trafficking of MC2R (2,3). Mutations in MC2R or MRAP cause familial glucocorticoid deficiency (FGD).…”
Section: Introductionmentioning
confidence: 99%